الصناديق الدولية للتعويض كآلية لإصلاح الأضرار البيئية الناجمة عن نشاط السفن - تركي, ليدية (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تهدف هذه الدراسة إلى تبيان الدور الذي تلعبه صناديق التعويض في تغطية الأضرار البيئية الناجمة عن نشاط السفن، في حالة عدم تمكن آليات المسؤولية التقليدية من إصلاح الضرر، ذلك من خلال الانطلاق من الإشكالية التي فحواها: ما مدى فعالية الصناديق الدولية للتعويض كآلية مكملة لقواعد المسؤولية المدنية في تغطية الأضرار البيئية الناجمة عن نشاط السفن؟ وقد خلص هذا البحث إلى مجموعة من النتائج، ومن ذلك، أنّ صناديق التعويض على الرغم من الدور الذي تلعبه في مجال تغطية الأضرار البيئية الناجمة عن نشاط السفن، إلا أنه تشكل في الوقت ذاته عبئا على عاتق المحتملين مما يفرض ضرورة تحقيق توازن بين مصلحة المضرور في الحصول على حقه في التعويض وبين العبء المالي الملقى على عاتق الشخص الملوث. This study aims to show the role that compensation funds play in covering environmental damages resulting from ship activity, in the event that the traditional liability mechanisms are unable to repair the damage, by starting from the problematic they covered: How effective are international compensation funds as a complementary mechanism to civil liability rules In covering the environmental damage caused by ship activity? This research concluded with a set of results, including that compensation funds, despite the role they play in covering environmental damage resulting from ship activity, are at the same time a burden on the prospects, which imposes the need to strike a balance between the interest of the injured in the Obtaining his right to compensation and the financial burden placed on the polluted person.